Charge transport and its characterization using photo‐CELIV in bulk heterojunction solar cells. Issue 1 (28th October 2016) - Stephen, Meera; Genevičius, Kristijonas; Juška, Gytis; Arlauskas, Kestutis; Hiorns, Roger C
Abstract: This mini‐review gives a simple overview of the workings of organic photovoltaic (OPV) devices, the way in which charge transfer occurs through the active layers, and then introduces how photo‐induced charge carrier extraction by linearly increasing voltage (photo‐CELIV) and time of flight (TOF) techniques can be employed to give comprehensive indications of charge carrier mobility, density and recombination in OPVs. It is shown how photo‐CELIV and TOF characterizations, using extraction current transients, can give an understanding of degradation mechanisms through observation of the trapping of charge carriers and bimolecular recombination. Examples of deployment and the interpretation of the results are given. It is hoped that this brief introduction will serve as a stepping stone into more in‐depth papers and books and encourage wider use of photo‐CELIV and TOF technologies which can be employed with whole devices. © 2016 Society of Chemical Industry Abstract : Photo‐CELIV and TOF are powerful techniques for characterizing charge transfer in whole organic photovoltaic cells. This mini‐review outlines how they work and gives examples of their use.